DETERMINATION OF PLANNING MANAGEMENT AND SCHOOL COMMITTEE PARTICIPATION IN IMPROVING THE QUALITY OF BASIC EDUCATION - Miftahul Arifin; Nur Khoiri; Widya Kusumaningsih (SOSIOEDUKASI, 2026)
This research is motivated by fluctuations in the quality of primary education in Godong District, which are influenced by internal governance and community participation. The study aims to analyze the influence of planning management and the role of school committees on educational quality, both partially and simultaneously. Using a quantitative correlational method, data were collected through questionnaires from a sample of public elementary schools in the area. The results of the regression analysis indicate that data-based planning management and the role of school committees as supporting agencies have a significant and positive influence on educational quality. Simultaneously, both variables contribute 66.52%, while 33.48% is influenced by other factors. In conclusion, the synergy between inclusive strategic planning and the revitalization of the committee's role as external leverage is a key determinant in improving educational quality standards in primary schools.